So close - Yuen, Cory (Quezon City : Magnavision.)
Get ready for one of the most dynamic, action-packed films of the year! Directed by famed action choreographer Cory Yuen (The Transporter, Jet Li's The Enforcer), So Close is a thrill-a minute shootout, with lightning-quick action sequences and great performances by Qi Shu (The Transporter), Zhao Wei (Shaolin Soccer) and Karen Mok (Black Mask). A crooked businessman brings in a pair of high-tech assassin sisters to murder his elder brother so he can take over the over the family's business empire. When a determined policeman starts to put the pieces of the puzzle together, the businessman realizes that he must destroy all evidence ... including the assassins and the cop! The three women are left to fight their lives, while helping each other along the way. With some of the best action scenes to appear on film this year, So Close is a high-octane blockbuster hit!